Case report: target antigen and subclass switch in a patient with autoimmune nodopathy - Appeltshauser, Luise; Glenewinkel, Helena; Rohrbacher, Sophia; Wessely, Lena; Villmann, Carmen; Sommer, Claudia; Doppler, Kathrin (Frontiers in Immunology, 2024)
Introduction Autoimmune nodopathy (AN) is a new entity in the field of peripheral neuropathies and is defined by the presence of auto-antibodies against structures of the node of Ranvier combined with specific clinico-pathophysiological features and therapy response in affected patients. The target-specific antibodies do not only serve as diagnostic biomarkers but also for treatment evaluation during follow-up. Case report We report a 66-year-old female patient with various autoimmune diseases, including a history of membranous glomerulonephritis which presented with acute-onset, sensorimotor tetraparesis, cranial nerve involvement, and mild respiratory insufficiency. Under the suspicion of Guillain–Barré syndrome, she received intravenous immunoglobulins (IVIg) and achieved remission. At 8 months later, she relapsed with now a poor response to IVIg and developed additional features such as severe sensory ataxia, tremor, and neuropathic pain. Anti-contactin-1 IgG2 antibodies were detected, and the diagnosis was reverted to AN. Plasma exchange and rituximab treatment led to a serological remission and corresponding significant clinical improvement, and the therapy was paused. At 2 years after symptom onset, her condition worsened again with sensorimotor symptoms and severe neuropathic pain despite seronegativity for contactin-1. However, serum binding assays to teased nerve fiber staining showed recurring antibody reactivity against paranodal structures. Caspr-1 was identified as a new target antigen via cell-based assay, and high-titer antibodies of the IgG4 subclass were confirmed via ELISA. Hence, a new cycle of plasma exchange and regular rituximab treatment was initiated, with subsequent clinical improvement and serological remission. The serum neurofilament light chain (sNFL) levels were assessed retrospectively and rose and fell together with the antibody titer. Discussion This case demonstrates that autoimmunity to (para)nodal structures can reoccur especially in patients prone to autoimmune disorders and can switch its target antigen and subclass in the course of disease. The presence of auto-antibodies against different targets at the node of Ranvier has direct implications for therapeutic management. We suggest a close follow-up of patients with AN after successful therapy. In case of deterioration despite seronegativity, non-specific tests such as teased fiber assays and repeated screening for different target antigens should be considered.